Research on fault location and state evaluation method of diagnostic function for power cable insulation defects based on the impedance spectrum - SI Jie; CHEN Zhi; ZHAO Jian; ZHOU Yuxiao (Diance yu yibiao)
In the detection of power cable insulation defects, the accurate location and degree evaluation of insulation defects are crucial to the planned overhaul work of power cable. Taking XLPE coaxial cable as an example, in this paper, based on the transmission line distribution parameter model and the integral transformation theory, the impedance spectrum function of the power cable is decomposed through the e-2γx function system in the space domain, and a diagnostic function for insulation defects is proposed. By investigating the relationship between insulation defects and insulation defect function, an insulation defects detection method is proposed for the location and degree evaluation of L/C type insulation defects in power cable. The feasibility of the proposed detection method is verified by a simulation example, which can accurately locate and evaluate the degree of the insulation defects.